IMPLEMENTASI TEKNIK PROYEKSI PENDIDIKAN PADA PROGRAM STUDI PENDIDIKAN AGAMA ISLAM IAIN KEDIRI TAHUN 2018/2019 – 2027/2028 - Nurul Hudha Purnomo (Edudeena : Journal of Islamic Religious Education, 2019)
Abstract: Management of students is an act of managing students since the first time they enroll in the institution until their graduation using effective and efficient ways so that they can achieve the educational goals set by the institution. In the process of management of students, the first thing to do is planning. At the planning stage, there is a process of determining future plan, which one of its methods is education projection. Projections are estimations of future conditions using existing data. The method used in the projection is to use the growth rate (AP), while the data is taken from the number of new students and graduates of the Islamic Education (PAI) study program, using the assumptions of upward targets. The result of the education projections on the number of new students obtained by the AP data is 0.6 percent. This result was used to carry out projections for the next 9 years so that the target in 2027 would be obtained by 460 students. The AP data for PAI alumni is 9.94 percent. This data is used to carry out projections, so that by 2027 it is targeted that the number of graduates will increase to 460 students. This data is expected to be useful to determine the planning of the number of lecturers, facilities and infrastructure. Abstrak: Manajemen peserta didik adalah pengelolaan peserta didik mulai dari saat peserta didik masuk di institusi sampai dengan lulus perkuliahan secara efektif dan efisien sehingga dapat mencapai tujuan pendidikan yang telah ditetapkan oleh institusi. Pada proses manajemen peserta didik hal yang pertama kali dilakukan adalah perencanaan , pada tahap perencanaan terdapat proses menetapkan rencana pada masa datang salah satu metode yang dilakukan adalah proyeksi pendidikan. Proyeksi adalah perkiraan tentang kondisi yang akan datang dengan menggunakan data yang ada. Metode yang digunakan dalam proyeksi adalah dengan menggunakan angka pertumbuhan (AP), data yang digunakan jumlah mahasiswa baru dan lulusan program studi Pendidikan Agama Islam (PAI). Asumsi yang digunakan menggunakan target naik. Hasil dari proyeksi pendidikan pada jumlah mahasiswa baru diperoleh AP data sebesar 0,6 persen, hasil ini digunakan untuk melakukan proyeksi 9 tahun kedepan sehingga didapatkan target pada tahun 2027 sejumlah 460 mahasiswa. AP data untuk alumni PAI adalah sebesar 9,94 persen, data tersebut digunakan untuk melakukan proyeksi, sehingga pada tahun 2027 ditargetkan jumlah lulusan meningkat menjadi 460 mahasiswa. Data ini diharapkan dapat berguna untuk menentukan rencana jumlah dosen, sarana dan prasarana.